Association of Residual Stromal Tumour Infiltrating Lymphocytes with Pathological Response Following Neoadjuvant Chemotherapy in Breast Carcinoma: A Retrospective Cohort Study - K Hari Krishna; MS Supreetha; A Hemalatha; PN Sreeramulu (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Tumour Infiltrating Lymphocytes (TILs) are important indicators of the host immune response and established predictive biomarkers primarily in Triple-Negative Breast Cancers (TNBC) and Human Epidermal Growth Factor Receptor 2 (HER2) - positive Breast Cancers (BC), but not across all BC subtypes. However, the biological and clinical significance of residual stromal TILs following Neoadjuvant Chemotherapy (NACT) remains incompletely understood. Unlike pre-treatment TILs, residual stromal TILs reflect the posttreatment tumour immune microenvironment and may provide additional information on pathological response and residual disease burden. Evaluating residual stromal TILs on routine Haematoxylin and Eosin (H&E)-stained sections offers a simple, reproducible, and cost-effective approach that could enhance routine pathological assessment. Aim: To evaluate the distribution of residual stromal TILs in postneoadjuvant surgical resection specimens and its association with pathological response. Materials and Methods: This retrospective cohort study was conducted at the Department of Pathology, Sri Deveraj URS Medical College, Kolar, Karnataka, India, from January 2021 to January 2025. A total of 47 patients with histopathologically confirmed BC treated with NACT followed by surgery. Residual stromal TILs were evaluated in residual invasive tumour on post-treatment resection specimens using H&E sections, in accordance with International Immuno-oncology Biomarker Working Group recommendations, and categorised as low (50%). Pathological response was assessed using the Miller-Payne Grading System (MPGS) and Residual Cancer Burden (RCB) classification. Associations between residual stromal TIL categories and treatment response were analysed using Fisher’s-exact test and Spearman’s rank correlation coefficient. Results: Among the 47 patients, low residual stromal TILs were identified in 17 (36.2%), intermediate residual stromal TILs in 17 (36.2%), and high residual stromal TILs in 13 (27.6%). Pathological Complete Response (pCR) was achieved in 4 (8.5%) patients. No statistically significant association was observed between residual stromal TIL category and pCR (Fisher’s-exact test, p=0.36). Residual stromal TIL category demonstrated a moderate positive correlation with MPGS (Spearman’s ρ=0.56, p